Optimisation of Distribution Network Applying Logistic Outsourcing - Ivaković, Čedomir; Stanković, Ratko; Šafran, Mario (Promet - Traffic&Transportation, 2012)
The problem of forming the distribution network results from the need to harmonize the characteristics of efficiency and efficacy of the supply chain with the corporate competition strategy. In this sense the possibility of optimising the distribution network has been presented (on a mathematical model) by applying the logistic outsourcing. The optimisation has been carried out using MS Excel software tools Solver. The results of the analysis have shown that possibilities for the reduction of distribution costs need to be searched for primarily in the domain of transport, in the target segment of the distribution network. The improvement elements have been achieved by outsourcing part of the supply chain, i.e. by introducing the cross-docking system which is managed by the external supplier of the logistic services. Quantitative changes, apart from the redistribution of the traffic of logistic and distribution centres and the reduction of logistic costs, have been reflected also in the geographical arrangement of distribution. The logistic outsourcing had dominant impact on the formation of the distribution network. KEY WORDS: distribution network, optimisation, logistic outsourcing